Pengaruh Konseling Gizi Terhadap Perilaku Gizi, Kadar Gula Darah, Dan Kadar Hba1c Pada Diabetisi Rawat Jalan Rsup Prof Dr R.D Kandou Manado - Olga Lieke Paruntu; Olfie Sahelangi; Stifriandy E. Palit (Jurnal GIZIDO, 2018)
Diabetes Mellitus is a chronic disease that occurs when the body can not produce enough insulin or can not effectively use, Control and treatment of diabetes mellitus include blood sugar control, HbA1c levels, and good nutritional behavior. Control and processing is essential for diabetics, the importance of knowledge, understanding, and information for influential disease management in disease control and treatment, in this study knowledge, understanding, and information obtained through nutritional counseling. This study aims to determine differences in nutritional behavior, blood sugar levels and levels of HbA1c before and after counseling on an outpatient diabetic from RSUP Prof Dr R.D Kandou Manado. The type of research used is quasi experimental research. According to Saryono (2011), the design of this type of research uses only one subject group, the measurement is done before and after the treatment. The difference of the two measurement results is considered as the treatment effect, the sample size is 30 people, the measurement of blood glucose and HbA1c using the result of the laboratory examination conducted by the hospital and the nutritional behavior is measured by the research questionnaire. The result of this research concluded that there is influence of nutritional counseling to blood sugar level with p value 0.000 (p <0.05), there is influence of nutrition counseling to HbA1c with p value 0.000 (p <0.05), and there is influence of nutrition counseling to nutrient behavior with p value 0.000 (p <0.05).